Overcoming the Limitations of MXene Electrodes for Solution‐Processed Optoelectronic Devices (Adv. Mater. 41/2022). Issue 41 (13th October 2022) - Zhou, Huanyu; Han, Shin Jung; Lee, Hyeon‐Dong; Zhang, Danzhen; Anayee, Mark; Jo, Seung Hyeon; Gogotsi, Yury; Lee, Tae‐Woo
Abstract : MXene Electrodes Various applications of MXenes have been intensively explored, except in optoelectronics, in which poor environmental stability severely impedes its practical application. In article number 2206377, Yury Gogotsi, Tae‐Woo Lee, and co‐workers report a new approach to improve the environmental stability, and electrical characteristics of MXene electrodes and then demonstrate their applications in large‐area optoelectronic devices.